PENGARUH STRUKTUR AKTIVA, PROFITABILITAS, UKURAN PERUSAHAAN, DAN LIKUIDITAS TERHADAP STRUKTUR MODAL PADA PERUSAHAAN MANUFAKTUR , TAHUN 2014-2018 - Alphonsius Umbu Manja; Eka Putri Suryantari (Badung: LPPM Universitas Triatma Mulya, 2020)
This study aims to determine how the influence of asset structure, profitability, company size, and liquidity on capital structure partially or simultaneously. The data used in this study were taken from financial reports that can be accessed on the Indonesia Stock Exchange (IDX) or www.idx.co.id and their respective websites from the manufacturing companies in the cosmetics and household equipment< subsector. Sampling uses a purposive sampling technique and gets the results of 5 company samples that fit the research criteria. The analysis technique used is multiple linear regression analysis. The results of this study indicate that partially the asset structure has no significant effect on the capital structure with the calculated T calculation value of 1.664, and a significant value of 0.112, profitability has a significant effect on the capital structure with the calculation result of the calculated T value of -3.720 and a significant value of 0.001, company size has a significant effect on capital structure with the calculated T value of - 2,950 and a significant value of 0.008, and the liquidity has a significant effect on the capital structure with a calculated T value of -8,082 and a significance value of 0,000. While the simultaneous structure of assets, profitability, company size, and liquidity have significant effect on capital structure with the calculated F calculation of 34.620 and a significant value of 0.000.